2010 43rd Hawaii International Conference on System Sciences 2010
DOI: 10.1109/hicss.2010.146
|View full text |Cite
|
Sign up to set email alerts
|

Developing Reliable Measures of Privacy Management within Social Networking Sites

Abstract: Besides providing a benefit for future study of SNS, reliable, valid measures are urgently needed due to the unprecedented scale of participation in these sites. SNS have memberships that number in the tens of millions, drawing from countries around the globe [7].It can be argued SNS are the largest examples of information systems that have ever existed. Some information systems theories, such as the Technology Acceptance Model, have been applied to social computing applications [40], but these efforts show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 21 publications
1
86
0
Order By: Relevance
“…Dwyer, Hiltz and Passerini (2007) investigated the use of Facebook by college students with an average age of 20.4 ( n = 69) and found that more than half of the users accessed Facebook every day, and 82% updated their profiles on a daily basis. Selwyn (2009) found that university students ( n = 909) used Facebook mainly for reflecting on the university experience, exchange of practical and academic information, and displaying supplication or disengagement.…”
Section: Literature Review On Facebookmentioning
confidence: 99%
“…Dwyer, Hiltz and Passerini (2007) investigated the use of Facebook by college students with an average age of 20.4 ( n = 69) and found that more than half of the users accessed Facebook every day, and 82% updated their profiles on a daily basis. Selwyn (2009) found that university students ( n = 909) used Facebook mainly for reflecting on the university experience, exchange of practical and academic information, and displaying supplication or disengagement.…”
Section: Literature Review On Facebookmentioning
confidence: 99%
“…A study of Facebook privacy concerns determined that users practice poor privacy control of their information and third parties were consistently trying to obtain users' information (Jones & Soltren, 2005). Dwyer, Hiltz, and Passerini (2007) found that when comparing the privacy practices of MySpace users to Facebook users, those who used Facebook were more trusting of the website and therefore more likely to disclose identifying information on their profiles.…”
Section: Online Privacy Managementmentioning
confidence: 99%
“…After the decision to join a social networking site, people even revealed information they were very concerned about being known by strangers (Acquisti & Gross, ). In fact, there is little or no relation between perceived Internet privacy concerns and amount of disclosure (Dwyer et al, ). However, people did not restrict self‐disclosure itself, but adjusted the visibility of their profiles for others by changing their privacy settings to avoid undesired audiences (Tufekci, ; Utz & Krämer, ).…”
Section: Self‐presentation In Common‐bond Communitiesmentioning
confidence: 99%